Abrupt transition to heightened poliomyelitis epidemicity in England and Wales, 1947–1957, associated with a pronounced increase in the geographical rate of disease propagation - Smallman-Raynor, Matthew; Cliff, A.D. (Cambridge University Press, 2014)
The abrupt transition to heightened poliomyelitis epidemicity in England and Wales, 1947–1957, was associated with a profound change in the spatial dynamics of the disease. Drawing on the complete record of poliomyelitis notifications in England and Wales, we use a robust method of spatial epidemiological analysis (swash-backwash model) to evaluate the geographical rate of disease propagation in successive poliomyelitis seasons, 1940–1964. Comparisons with earlier and later time periods show that the period of heightened poliomyelitis epidemicity corresponded with a sudden and pronounced increase in the spatial rate of disease propagation. This change was observed for both urban and rural areas and points to an abrupt enhancement in the propensity for the geographical spread of polioviruses. Competing theories of the epidemic emergence of poliomyelitis in England and Wales should be assessed in the light of this evidence.